Recognising and managing increased HIV transmission risk in newborns - Max Kroon (AOSIS, 2015)
Prevention of mother-to-child transmission (PMTCT) programmes have improved maternalhealth outcomes and reduced the incidence of paediatric HIV, resulting in improved childhealth and survival. Nevertheless, high-risk vertical exposures remain common and areresponsible for a high proportion of transmissions. In the absence of antiretrovirals (ARVs),an 8- to 12-hour labour has approximately the same 15% risk of transmission as 18 monthsof mixed feeding. The intensity of transmission risk is highest during labour and delivery;however, the brevity of this intra-partum period lends itself to post-exposure interventions toreduce such risk. There is good evidence that infant post-exposure prophylaxis (PEP) reducesintra-partum transmission even in the absence of maternal prophylaxis. Recent reports suggestthat infant combination ARV prophylaxis (cARP) is more efficient at reducing intra-partumtransmission than a single agent in situations of minimal pre-labour prophylaxis. Guidelinesfrom the developed world have incorporated infant cARP for increased-risk scenarios. Incontrast, recent guidelines for low-resource settings have rightfully focused on reducingpostnatal transmission to preserve the benefits of breastfeeding, but have largely ignored thepotential of augmented infant PEP for reducing intra-partum transmissions. Minimal prelabourprophylaxis, poor adherence in the month prior to delivery, elevated maternal viralload at delivery, spontaneous preterm labour with prolonged rupture of membranes andchorioamnionitis are simple clinical criteria that identify increased intra-partum transmissionrisk. In these increased-risk scenarios, transmission frequency may be halved by combiningnevirapine and zidovudine as a form of boosted infant PEP. This strategy may be important toreduce intra-partum transmissions when PMTCT is suboptimal.